Design of smart product to reduce pollution caused by solid waste on Costa Rican beaches - Meza-Blanco, Aurora (2022)
Costa Rica is a country whose economy is largely based on national and international tourism that reaches its attractions. The main attraction are the beaches of both Pacific and Caribbean coasts. However, the increase in waste is present in these, had become a danger to visitors and the ecosystem. In the case of visitors, it can cause injuries, affect public health and reduce the attractiveness of touristic sites. For the ecosystem, garbage increases its degradation, ghost fishing and animal malnutrition. The design process was lead using the design thinking methodology. After completing all stages (problem investigation, definition of functionality, solution ideation and prototyping), Suia is finally created: an intelligent product for public use which represents a better option for collecting wastes generated by visitors compared to the actual garbage cans. Suia can achieve this thanks to its intelligent functions of mobilization and its practical functions of storage, waste separation and resistance to environmental factors. With its implementation, Suia is expected to contribute to reduction of waste generated by visitors and to provide a better experience and help in the conservation of the environment.